SENTINEL IMAGE APPLICATION FOR ASSESSMENT OF MACROALGAE CONDITIONS AT BONE MALAYA, MAKASSAR CITY 2015-2020 - Raj, Mayang Nizhar; Selamat, Muh Banda; La Nafie, Yayu Anugrah; Nurdin, Nurjannah; Mashoreng, Supriadi (Hasanuddin University, 2022)
This study was aimed to analyze and map the presence and percent cover of macroalgae in Bone Malalaya to determine the condition before and after the construction of the new port, as well as to analyze the distribution of suspended solids loads and environmental parameters and their relationship to changes in macroalgae cover in Bone Malalaya. The image used in this research is sentinel imagery 2A level 2A with the acquisition date of 28 October 2015, 14 July 2018 and 10 December 2020 which was processed using geographic information software to obtain a map of algae cover in Bone Malalaya. Sampling of water and physical parameters at the research location was carried out at 8 sampling stations, while algae sampling stations were carried out at 3 stations and 9 substations. There were no seagrass found in the research location, but algae species of Sargassum sp. With cover changes based on the calculation of image pixels, namely 36.49 Ha in 2015, 26.45 Ha in 2018 and 35.73 Ha in 2020. The highest Total Suspended Solid value at the study site was at station 8 with a value of 33.1 mg/L and the lowest value was at station 1 with a value of 16.3 mg/L. Seagrasses were not found at the research site due to unsupported physical parameters and port activities that interfere with seagrass life. The presence of macroalgae Sargassum sp at the research site is assumed because Sargassum sp has a high tolerance for physical parameters that exceed the quality standards set by the Ministry of Environment in 2004.